2009
DOI: 10.1007/s12272-009-2213-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and assessment of food-borne pathogenic bacteria in frozen foods

Abstract: One hundred ninety-three frozen food samples collected in Korea various public bazaars from October 2006 to September 2007. Staphylococci were detected in 21.8% of frozen food samples. Staphylococcus aureus was isolated from 17 (8.8%) samples. Other staphylococci isolates were identified as S. warneri (7.8%), S. epidermidis (2.1%), S. xylosus (1.6%), S. eguorum (1%), and S. vitulinus (0.5%). Additionally, the antimicrobial susceptibility of 42 staphylococcal isolates to ten different antimicrobial agents was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Mupirocin is used as a topical treatment for bacterial skin infections. Therefore, it is useful in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) [8]. Resistance to mupirocin among Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Mupirocin is used as a topical treatment for bacterial skin infections. Therefore, it is useful in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) [8]. Resistance to mupirocin among Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial susceptibility of S. aureus isolated from various food samples to new agents (linezolid and quinupristin-dalfopristin) has been investigated only in several countries. New agents showed good activity against S. aureus isolated from frozen food samples collected in Korea (Baek et al, 2009). White et al (2003) also reported that all S. aureus isolated from commercial broilers in northeastern Georgia were susceptible to linezolid and quinupristin-dalfopristin.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance pattern of S. aureus to quinolones and new agents has been investigated in S. aureus in various clinical studies (Sader et al, 2001;Jevitt et al, 2003;Madhusudhan et al, 2003;Jorgen et al, 2007;Hidalgo et al, 2008;Jacobs et al, 2009;Japoni et al, 2010), whereas less information has been reported on antimicrobial activity of these agents in food isolates (White et al, 2003;Baek et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Frozen foods do not need any additional additives since microorganisms do not develop when the temperature of the food is beneath −9.5 °C (15 °F), which is adequate in forestalling food deterioration. Most microbes do not increase at frigid temperature and a large number of these microorganisms die because their enzymes do not work appropriately to keep up ordinary cell activities (Baek et al, 2009). Freezing is the prevailing method of preserving high quality in foods.…”
Section: Introductionmentioning
confidence: 99%